Improving STEM Literacy on the Topic of Organic Solar Cells Through an AI-Powered Personalized Learning Platform: A Case Study of Pre-Physics Teachers - Arip Nurahman; Eka Cahya Prima; Ida Kaniawati; Endi Suhendi; Nizar Alam Hamdani; Ali Ismail; Surya Gumilar; Irma F A; Lasmita Sari; Rizal Adimayuda (Proceedings Series of Educational Studies, 2023)
In an era where Science, Technology, Engineering, and Mathematics (STEM) education holds pivotalimportance, this research endeavors to explore innovative approaches to enhance STEM literacy,with a specific focus on the topic of organic solar cells. This study presents a case study conductedamong pre-physics teacher students to improve their understanding of this critical topic byintegrating an AI-powered personalized learning platform. The research is grounded in the beliefthat personalized learning, augmented by artificial intelligence, can offer tailored and engagingeducational experiences. By targeting pre-physics teacher students, this study not only addressesthe fundamental STEM knowledge gap but also aims to contribute to the development of proficienteducators who can effectively impart this knowledge to future generations. The study methodologyinvolves the implementation of an AI-powered personalized learning platform designed to adapt tothe individual learning needs and preferences of the participants. Data is collected from pre- andpost-intervention assessments, as well as feedback from the participants, to evaluate the platform'seffectiveness. Preliminary findings demonstrate significant improvements in STEM literacy relatedto organic solar cells among the pre-physics teacher students. The AI-powered platform, by offeringcustomized content, feedback, and learning pathways, has been instrumental in elevating theircomprehension of this complex subject matter. This research not only contributes to the field of AIenhancededucation but also offers insights into the potential of personalized learning platforms inimproving STEM literacy. The findings have implications for curriculum development, teachertraining, and the broader quest for fostering STEM competence among the next generation ofeducators. In conclusion, the study underscores the promise of AI-powered personalized learningplatforms in augmenting STEM education, explicitly enhancing the understanding of organic solarcells among pre-physics teacher students.